On Applying Virtual Reality to Underwater Robot Tele-Operation and Pilot Training - Lin, Qingping; Kuo, Chengi (International Journal of Virtual Reality, 2001)
Virtual reality systems are being increasingly used for enhancing human perception of complex real-world or synthetic events. Serious applications outside entertainment range from education training to science and engineering. In this paper, we present our research work concerning the use of virtual reality in underwater robot tele-operation and training. We have proposed a novel concept of ROV safety domain to overcome the robot sensor error issue involved in virtual environment based underwater teleoperation approach. The detailed mathematical model of the ROV safety domain and its proof will be presented. In addition, we will examine how ROV safety domain can be used in underwater robot teleoperation, and present the architecture of our prototype virtual tele-operation system. Its current status and evaluation, as well as issues involved in its practical application will also be discussed.